Analysis of Disruption, Resilience, and Reconfiguration of Global Value Chains in the Post-COVID Era under Geopolitical Pressures: A Systematic Literature Review - Wefielananda, Rahmi Afzhi (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze the forms of disruption, the factors influencing resilience, and the reconfiguration strategies of Global Value Chains (GVCs) in the post-COVID-19 era amid increasing global geopolitical pressures. The study employs a Systematic Literature Review (SLR) methodology following the PRISMA guidelines. The literature search was conducted using the Scopus database with keywords related to global supply chain disruptions, the COVID-19 pandemic, and geopolitical tensions. Of the 368 articles initially identified, 89 met the inclusion criteria and were included in the final synthesis. The findings reveal that post-pandemic GVC disruptions can be categorized into six major types: production disruptions, logistics disruptions, trade disruptions, geopolitical disruptions, energy disruptions, and environmental and climate-related disruptions. Factors influencing GVC resilience include operational, organizational, network, and technological dimensions. Furthermore, the most frequently identified reconfiguration strategies in the literature include supplier and production location diversification, supply chain regionalization, interorganizational collaboration, enhanced risk management, and supply chain digitalization. These findings suggest that scholarly attention has shifted from an efficiency-oriented perspective toward strengthening the resilience of global value chains in response to increasingly complex uncertainties. This study provides a comprehensive synthesis of the evolving literature on GVC disruption, resilience, and reconfiguration and offers valuable insights for future research and policymaking.